Research on the Relationship between Religious Belief and Social Morality - Maheswari, Uma (Journal of Social Science and Humanities, 2024)
Deoris are a fascinating minor tribal group of Northeast India, known for their unique way of life and religious practices. Since ancient times, they have strongly believed in sacrificial rituals of religion. After the downfall of the Chutiya Kingdom, this group of people were displaced from their original habitat and started to settle in various places of upper Assam. Today, these groups of people are scattered in various districts of Assam and Arunachal Pradesh. Wherever they settle, they build a temple there as it is the centre for their people where they worship all gods and goddesses. To worship in their temples, they have different Pujari. They performed different rituals in their temples. They worship their gods by singing Hymns. In earlier times when they lived in Kundil Nagar they had four sub - groups of people worshiped at four different Deohals. The Deoris living on the bank of river Dibang worshipped Kundi - Mama, Gira - Girasi, or Bura - Buri, the Borgoiyas were at the Tamreswari Temple, and the Tengaponiyas were at the Boliya - Baba temple. Patorgoiyas were worshipped at the temple of PatSadiya during the reign of Gaurinath Singha (1780 - 94). Deoris are an essential part of the rich cultural heritage of northeast India, and their way of life and religious beliefs are truly unique.